An analytical study about the operational effectiveness of the Covid Control Room in a Medical College of Northern India - Sehgal, Shruti; Manchanda, Gurdip Singh; Muzammil, Khursheed; Raghav, Santosh Kumar; Sehgal, Shreyak (Indian Journal of Community Health, 2022)
Muzzafarnagar Medical College (MMC), Muzzafarnagar was declared a designated covid hospital by the Uttar Pradesh State Government. A Covid Control Room (CCR) was hence established to manage the disaster. Aims & Objectives: The CCR worked as the operational brain of MMC. Study Setting: Muzzafarnagar Medical College, Muzzafarnagar, Uttar Pradesh, India. Study Design: A hospital record based observational study. Material Methods: A total of 1132 admitted covid positive patients in three months constituted the study population. The CCTV cameras were installed inside the isolation wards, and the ICUs with 24/7 video coverage. The DGME (Uttar Pradesh) developed the Patient Information System (PIS) wherein information was uploaded in a database and WhatsApp messages were sent to the relatives twice daily. Results: The CCR received on an average 200 calls per day. A total of 12,622 calls were received in two months. With, PIS in function the no. of calls received in CCR reduced drastically. 100% coverage of the patients’ information was achieved. Conclusion: The scope of the control room has expanded considerably to address various aspects of the covid-19 pandemic crisis. These findings will be helpful as a reference for future. It is one of the first studies and unique in nature.